Nutrition and enhanced sports performance : muscle building, endurance, and strength - Bagchi, Debasis, 1954-; Nair, Sreejayan; Sen, Chandan K. (Academic Press, an imprint of Elsevier, 2019)
Nutrition and Enhanced Sports Performance: Muscle Building, Endurance and Strength, Second Edition, includes comprehensive sections on the role of nutrition in human health, various types of physical exercises, including cardiovascular training, resistance training, aerobic and anaerobic exercises, bioenergetics and energy balance, and the nutritional requirements associated with each. Other sections cover sports and nutritional requirements, the molecular mechanisms involved in muscle building, an exhaustive review of various foods, minerals, supplements, phytochemicals, amino acids, transition metals, competition training, healthy cooking, physical training, and lifestyle and dietary recommendations for sports performance. This updated edition includes new chapters on mood, alertness, calmness and psychomotor performance in sports, extreme sports, natural myostatin inhibitor and lean body mass, the benefits of caffeine in sport nutrition formulations, the role of vitamin D in athletic performance, probiotics and muscle mass. Provides a comprehensive appraisal of the nutritional benefits of exercise in human health; Compiles chapters reviewing the nutritional prophylaxis in human health; Addresses performance enhancement drugs and sports supplements; Presents various types of physical exercises and addresses exercise and nutritional requirements in special populations; Discusses sports nutrition and the molecular mechanisms involved in muscle building; Contains an exhaustive review of various food, minerals, supplements, phytochemicals, amino acids, transition metals, small molecules and other ergogenic agents; Highlights the aspects of healthy cooking, physical training, lifestyle and dietary recommendations for sports performance